The struggling democracy of Bangladesh - Kabir, Amanullah (Dhaka : Adorn Publication, 2002)
Articles, chiefly on the political issues of Bangladesh, since its inception.
Keywords: Democracy -- Bangladesh; Bangladesh -- Politics and government